Static and Free Vibration Analysis of Laminated Composite Plates Using Isogeometric Approach Based on the Third Order Shear Deformation Theory. (22nd January 2014) - Li, Xinkang; Zhang, Jifa; Zheng, Yao
Abstract : Isogeometric analysis (IGA) based on nonuniform rational B-splines (NURBS) is applied for static and free vibration analysis of laminated composite plates by using the third order shear deformation theory (TSDT). TSDT requires C 1 -continuity of generalized displacements and NURBS basis functions are well-suited for this requirement. Due to the noninterpolatory nature of NURBS basis functions, a penalty method is applied to enforce the essential boundary conditions. The validity and accuracy of the present method are demonstrated through a series of numerical examples of isotropic and laminated composite plates with different shapes, boundary conditions, fiber orientations, lay-up numbers, and so forth. The obtained numerical results are compared with either the analytical solutions or other available numerical methods.